2020
DOI: 10.3171/2020.4.peds20131
|View full text |Cite
|
Sign up to set email alerts
|

3D pediatric cranial bone imaging using high-resolution MRI for visualizing cranial sutures: a pilot study

Abstract: OBJECTIVEThere is an unmet need to perform imaging in young children and obtain CT-equivalent cranial bone images without subjecting the patients to radiation. In this study, the authors propose using a high-resolution fast low-angle shot golden-angle 3D stack-of-stars radial volumetric interpolated breath-hold examination (GA-VIBE) MRI sequence that is intrinsically robust to motion and has enhanced bone versus soft-tissue contrast. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Saariko et al compared BB-MR imaging using a T1 VIBE sequence and CT in nine pediatric patients and concluded that BB-MR imaging is a valid alternative to 3D-CT in the preoperative evaluation of patients with craniosynostosis [23]. In a further study, Patel et al concluded that BB imaging using a GA-VIBE sequence on a 3 T MRI is a promising method to achieve CT-like 3D cranial bone images in 11 pediatric patients [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saariko et al compared BB-MR imaging using a T1 VIBE sequence and CT in nine pediatric patients and concluded that BB-MR imaging is a valid alternative to 3D-CT in the preoperative evaluation of patients with craniosynostosis [23]. In a further study, Patel et al concluded that BB imaging using a GA-VIBE sequence on a 3 T MRI is a promising method to achieve CT-like 3D cranial bone images in 11 pediatric patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Kuusela et al used the variant of BB imaging derived from a T1 VIBE sequence, which was acquired using two echo times (in phase and out of phase), and applied this sequence to a study group of 15 pediatric patients [13]. Moreover, a fast low-angle shot goldenangle 3D stack-of-stars radial VIBE-(GA-VIBE-) based sequence on a 3 T MRI, with similar TR/TE and a flip angle of 3°was applied and evaluated in 11 pediatric patients [14]; however, 3D reconstruction and post-processing of the BB sequences are fairly extensive and time consuming, which still limits the application in the clinical routine. This problem was approached by automated segmentation techniques; however, these techniques were applied to BB-MR images of the skull of adults.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional surface images provided by stereophotogrammetric photography allow for full representation of the entire contour of the head without ionizing radiation (Shah et al, 2011; Engel et al, 2012). As an aside, MR protocols, such as Black Bone MRI and GA-VIBE MRI, have been recently published as a new alternative to CT for pre- and postoperative evaluation of head shape (Patel et al, 2020; Saarikko et al, 2020). Three-dimensional photography has been shown to be equivalent to CT scans for anthropometric measurements (Mendonca et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional stereophotogrammetric photography is susceptible to hair artifacts as the child ages, which is not true with CT scans. Even though the risk of ionizing radiation can be significantly limited using special bone imaging protocols (Stewart et al, 2018), it seems clear that “ALARA” principles (As Low As Reasonably Achievable), as well as new MR protocols being developed, will only continue to favor limiting the use of CT for shape outcomes in studies of craniosynostosis outcomes (Patel et al, 2020; Saarikko et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers rated each statement using a 5-point Likert scale [26][27][28] (ranging from 1 to 5 points with 1 = strongly disagree and 5 = strongly agree) to assess each image. The score of each statement was aggregated into a total for each image.…”
Section: Testmentioning
confidence: 99%